The regulatory role of INSIG1 in testicular Sertoli cells in boars - Shaoxuan Zhang; Hang Zhou; Simin Liu; Jing Li; Dali Wang; Boxing Sun; Hao Sun; Shuang Liang (Theriogenology, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

WD repeat-containing protein 41 (WDR41) is involved in fertilization and interacts with IZUMO1 and JUNO - Wenjun Zhang; Yangyang Sun; Xu Li; Simin Liu; Huimin Su; Wanjin Xing (Theriogenology, 2026)

Aggregation-induced emission photosensitizers for photodynamic food packaging: Antibacterial mechanisms, material innovations, and applications - Wenxin Wang; Shutian Sun; Simin Fan; Qingfeng Yang; Dequan Zhang; Chengli Hou (Trends in Food Science & Technology, 2026)

Embryonic developmental toxicity and potential endocrine disruption in an estuarine benthic fish under binary and ternary exposures to organic ultraviolet absorbents - Yining Zhang; Jinzhi Ren; Luhang She; Chenyang Sun; Ziqiang Guan; Simin Xia; Jianjun Li; Jining Liu; Ying Peng (Environmental Pollution, 2026)

GPR45 Regulates Body Weight and Energy Homeostasis in Pro-opiomelanocortin Neurons - Yongyong Meng; Chengchen Hu; Tao Zhao; Simin Xie; Jing Cui; Lei Sun; Xiaohui Wu (Phenomics, 2026)

Astronomical and volcanic forcing of Paleocene carbon cycle perturbations in the Norwegian Sea Basin - Xiaoyue Zhang; David B. Kemp; Manuel Vieira; David W. Jolley; Simin Jin; Qing Liu; Zixin He; Xilei Sun; Chunju Huang (Global and Planetary Change, 2026)

Acetochlor disrupts the maternal effect of food restriction in lizards (Eremias argus): Evidence from intergenerational growth and embryonic development - Yue Zhang; Yufan Nie; Simin Yu; Yuping Liu; Hao Yang; Jiajing Sun; Dier Song; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Journal of Hazardous Materials, 2026)

Mobile genetic elements drive the assembly of high-risk resistance and virulence configurations at the riverine water–sediment interface - Jingru Yang; Xin Meng; Hongzheng Zhang; Wanchen Sun; Linzhen Yang; Simin Li (Environmental Research, 2026)

Convallatoxin ameliorates fibroblast-like synoviocytes-mediated synovial inflammation and joint destruction in rheumatoid arthritis by targeting IDH1 - Suling Liu; Huijuan Hu; Yu Kuang; Simin Chen; Kai Sun; Chenxi Peng; Ruiru Li; Fan Su; Liuqin Liang; Qian Qiu; Youjun Xiao; Hanshi Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Temperature and ethanol synergistically enhance microplastic release from disposable cups: mechanistic insights and health risk assessment of typical plastics - Simin Li; Linzhen Yang; Xin Meng; Wanchen Sun; Hongzheng Zhang; Jingru Yang (ENGINEERING Environment, 2026)

Provincial policy simulation for steel decarbonization in China: a modular CGE-3E3S coupling framework - Yibo Li; Juan Li; Simin Guo; Mei Sun (Environmental Modelling & Software, 2026)

Distinct assembly mechanisms, functional traits and pathogenic risks of the plastisphere microbiome in a freshwater lake: Evidence from Baiyangdian Wetland - Simin Li; Wanchen Sun; Xuguang Tian; Xin Meng; Linzhen Yang; Hongzheng Zhang; Jingru Yang (Journal of Environmental Chemical Engineering, 2026)

Microplastic pollution steers stochastic assembly and biases predicted C–N functional potentials in lake sediments - Simin Li; Jingru Yang; Xin Meng; Hongzheng Zhang; Wanchen Sun; Linzhen Yang (Journal of Environmental Chemical Engineering, 2025)

Chitosan-based coatings and films: Mechanisms and applications in postharvest preservation of mangoes - Guohui Yi; Simin Fan; Huanqi Wu; Ajahar Khan; Ruchir Priyadarshi; Wanying Sun; Derong Lin; Yiqin Zhang (Food Packaging and Shelf Life, 2025)

Insight into carbon-carbon coupling mechanism for syngas to higher alcohols over agglomeration-induced CuZn catalysts - Simin Du; Penglong Jia; Lei Sun; Chenyang Wang; Haijun Guo; Yongjun Liu; Hui Bai; Danni Xun; Maohong Fan; Wei Huang (Chemical Engineering Journal, 2025)

Analysis of low carbon transformation strategy and CO 2 emission metabolism in the steel industry - Yibo Li; Juan Li; Mei Sun; Simin Guo (Journal of Industrial Ecology, 2025)
As an energy‐intensive sector, the low‐carbon transformation of the steel sector plays a crucial role in achieving China's carbon neutrality goals. Therefore, exploring how learning strategies and incentive mechanisms can synergistically promote the transformation of production and energy structure in the steel sector toward net‐zero emissions is an urgent practical problem that needs to be solved. This study constructed an integrated evaluation framework that combines an improved dynamic computable general equilibrium model with input–output analysis and ecological network analysis, and incorporates learning strategies, carbon taxes, subsidies, carbon trading and other incentive mechanisms into the model to deeply analyze the transformation path of the steel sector in different scenarios. The research not only focuses on the low‐carbon transformation of the steel sector but also comprehensively analyzes the evolution of CO 2 emission metabolism and reveals the complex internal interactions under the background of emission dynamics through a multidimensional network perspective. The results indicate that the steel sector's production and energy structures have significantly changed by implementing incentive mechanisms and introducing learning strategies. In the scenario where carbon taxes, subsidies, and learning strategies work together, it is expected that by 2060, the share of short‐process steelmaking will reach 52.2%, while the proportion of carbon capture and storage equipped in long‐process will exceed 10%. At this time, the short‐process sector's control over other sectors and dependence on the system will increase.

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Thiol collectors removal from simulated tailings wastewater by batch electrocoagulation using copper electrodes - Gaogui Jing; Shenggui Zhao; Xinxing Liang; Huai Wang; Simin Yang; Wei Sun; Zhiyong Gao (Minerals Engineering, 2025)

Soil Water Accounting Network (SWAN): a novel neural network for modeling conceptual hydrological processes - Zheng Fang; Simin Qu; Ziheng Li; Qiongfang Li; Peng Shi; Yiqun Sun; Xiaoqiang Yang; Han Tang; Junfang Zhang; Zhengxian Zhu; Hongshi Wu; Weimin Bao (Journal of Hydrology, 2025)

Naringenin-loaded Flammulina velutipes chitin-glucan complexes gel system: structural modulation and dual lipid-lowering mechanisms - Simin Feng; Shuqi Liang; Jianyu Yang; Jiahao Yu; Yang Lin; Yizhen Xie; Peilong Sun; Ping Shao (Food Chemistry, 2025)

Human gut Bifidobacterium longum subsp. suillum is enriched in vitro by a pectic polysaccharide isolated from the flowers of Lilium lancifolium - Meixia Li; Renjie Liu; Tao Wang; Lana Duo; Guo Chen; Mengfei Mao; Yue Sun; Yun Li; Simin Cai; Wanqi Zhou; Haibiao Lai; Kan Ding (Carbohydrate Polymers, 2025)

Novel microbial fuel cell integrating anoxic/oxic-membrane bioreactor design for simultaneous energy recovery and carbon–nitrogen removal from shale oil and gas wastewater - Simin Zhou; Guangzhi Wang; Likun Huang; Shaofang Li; Chaopeng Li; Rui Zhao; Xiyu Sun; Dongdong Wang (Bioresource Technology, 2025)

A synergistic water-saving strategy combining stage-specific irrigation and application of exogenous thiamine enhances drought resistance of Xinjiang cotton - Fuxiang Zhao; Linjie Xia; Simin Sun; Hang Li; Yuxuan Rong; Yuxin Wang; Xuwen Wang; Xianhui Kong; Longfu Zhu; Xianlong Zhang; Yu Yu; Xiyan Yang (Plant and Soil, 2025)

Protective effects of berberine on MASLD: regulation of glucose and lipid metabolism through PI3K/Akt and STING pathways - Jing Ji; Ying Li; Tian Xu; Qi Shao; Zijin Sun; Simin Chen; Di Zhang; Qingguo Wang; Xueqian Wang; Chongyang Ma; Fafeng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Embryonic developmental toxicity to estuarine fish: Single and co-exposure to EHMC and its phototransformation products in Mugilogobius chulae - Jinzhi Ren; Luhang She; Chenyang Sun; Yining Zhang; Yimeng Wang; Simin Xia; Caixia Gao; Jianjun Li; Xiangping Nie; Ying Peng (Environmental Research, 2025)

Boosting capacitive energy storage performance of bismuth sodium titanate-based lead-free ceramics under low electric field - Fei Yan; Xin Qi; Jin Qian; Simin Wang; Cheng Shi; Zixiong Sun; Weiwei Wang; Ke Cao (Chemical Engineering Journal, 2025)

Characterization and removal of surface oligomers on polyester yarns dyed in decamethylcyclopentasiloxane waterless dyeing system - Simin Sun; Liujun Pei; Qinggai Zhang; Hao Li; Mingxuan Yang; Gang Sun; Jiping Wang (Journal of Environmental Chemical Engineering, 2025)

Structure of myelin in the central nervous system and another possible driving force for its formation—myelin compaction - Qi Shao; Simin Chen; Tian Xu; Yuyu Shi; Zijin Sun; Qingguo Wang; Xueqian Wang; Fafeng Cheng (Journal of Zhejiang University-SCIENCE B, 2025)

Removal of heavy metals from water by adsorption on metal organic frameworks: Research progress and mechanistic analysis in the last decade - Fang Yuan; Dingfan Yan; Shuaibo Song; Jinbo Zhang; Yangyang Yang; Zheng Chen; Jiahao Lu; Simin Wang; Yongjun Sun (Chemical Engineering Journal, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Estimation of pollution sources and hydraulic conductivity field in a coastal aquifer under tidal effects - Chao Wu; Simin Jiang; Xuemin Xia; Yue Sun; Zhi Li; Mengdie Ju; Si Li; Shihui Liu (Marine Georesources & Geotechnology, 2024)

Investigating the potential of EMA-embedded feature selection method for ESVR and LSTM to enhance the robustness of monthly streamflow forecasting from local meteorological information - Lei Xu; Peng Shi; Hongshi Wu; Simin Qu; Qiongfang Li; Yiqun Sun; Xiaoqiang Yang; Peng Jiang; Chao Qiu (Journal of Hydrology, 2024)

Novel synthesis of CuFe2O4/g-C3N4 based on microwave ferromagnetic resonance effect for the thorough removal of TC in mariculture wastewater under natural sunlight - Xiyu Sun; Huanzhang Feng; Guangzhi Wang; Likun Huang; Dongdong Wang; Simin Zhou; Rui Zhao (Chemical Engineering Journal, 2024)

Numerical Investigation into the Stability of Offshore Wind Power Piles Subjected to Lateral Loads in Extreme Environments - Miaojun Sun; Zhigang Shan; Wei Wang; Simin Xu; Xiaolei Liu; Hong Zhang; Xingsen Guo (Journal of Marine Science and Engineering, 2024)
Monopile foundations are extensively utilized in the rapidly expanding offshore wind power industry, and the stability of these foundations has become a crucial factor for ensuring the safety of offshore wind power projects. Such foundations are subjected to a myriad of complex environmental loads during their operational lifespan. Whilst current research predominantly concentrates on the effects of wind, wave, and current loads on monopile stability in extreme environments, it is imperative to consider the potential influence of unexpected submarine landslide loads. In this study, we provide a comprehensive overview of wind, wave, current, and submarine landslide loads on monopile foundations in extreme environments. Subsequently, we establish a finite element model for analyzing the stability of monopiles under complex lateral loads, and validate the accuracy of the model by comparing it with the previous numerical findings. A case study is performed with reference to the Xiangshui Wind Farm project to analyze the effects of varying submarine landslide densities, velocities, impact heights, and seabed sediment strengths on pile head horizontal displacement, pile rotation at the mudline, and maximum bending moment. The findings indicate that the increase in submarine landslide density, velocity, and impact height leads to an increase in horizontal displacement at the pile head, pile rotation at the mudline, and maximum bending moments, and a horizontal failure mode is observed in seabed sediments. Furthermore, under the same load conditions, a decrease in seabed sediment strength and internal friction angle triggers instability in monopiles, with a noteworthy transition from horizontal failure to deep-seated seabed sediment failure. Finally, we propose a criterion for monopile instability under diverse loading conditions.

Efficient zero wastewater and salt-free of cotton fiber dyeing via hydrophobic organic chemical/water two-phase dyeing system - He Zhu; Liujun Pei; Jingyuan Yi; Simin Sun; Qiushuang Hu; Jiping Wang; Zongqian Wang (Journal of Cleaner Production, 2024)

Enhanced photogenic self-cleaning of superhydrophilic Al2O3@GO-TiO2 ceramic membranes for efficient separation of oil-in-water emulsions - Dongdong Wang; Likun Huang; Haiyang Sun; Shaofang Li; Guangzhi Wang; Rui Zhao; Simin Zhou; Xiyu Sun (Chemical Engineering Journal, 2024)

Activated carbon fibers functionalized with superhydrophilic coated pDA/TiO2/SiO2 with photoluminescent self-cleaning properties for efficient oil-water separation - Dongdong Wang; Likun Huang; Hanxiao Fang; Shaofang Li; Guangzhi Wang; Simin Zhou; Rui Zhao; Xiyu Sun (Journal of Hazardous Materials, 2024)

Investigation and improvement of electrochemically activated peroxydisulfate systems for treating incineration leachate - Simin Zhou; Guangzhi Wang; Xi Chang; Likun Huang; Dongdong Wang; Rui Zhao; Xiyu Sun (Process Safety and Environmental Protection, 2024)

Comparative miRNA-seq analysis revealed molecular mechanisms of red color formation in the early developmental stages of Plectropomus leopardus - Xi Liu; Mouyan Jiang; Simin Wen; Kaixiang Zhang; Yucong Hong; Kaihui Sun; Xianwu Deng; Yang Huang; Gang Shi; Changxu Tian; Huapu Chen; Guangli Li; et al. (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play important roles in several biological processes, including the regulation of body color. Leopard coral grouper ( Plectropomus leopardus ) is a valuable marine aquaculture fish; however, at present, there are no published reports on its early body color development. The skin color of P. leopardus undergoes a transition from transparent to red from 26 days post-hatching (dph) to 30 dph. In this study, we performed miRNA sequencing on 26 dph (Transparent, PT) and 30 dph (Red, PR) skin samples of P. leopardus to explore the molecular mechanism underlying red color formation. A total of 44.31 M and 37.55 M clean tags were obtained from PT and PR group, respectively. Among these tags, 981 miRNAs were identified, including 493 known and 488 novel miRNAs. A total of 106 differentially expressed miRNAs (DEMs) were identified in PT vs. PR, with 43 up-regulated and 63 down-regulated miRNAs in the PR group, compared to the PT group (|fold change| > 2 and p-value < 0.05). A miRNA-mRNA network based on 18 candidate miRNAs and 53 target genes related to pigmentation, and KEGG enrichment analysis of the target genes of all DEMs, revealed that miRNAs involved in the formation of red skin color were mainly related to: 1) the inhibition of melanin synthesis (miR-141-z, miR-206-z, miR-206-y, miR-27-z, miR-137-y, miR-204-x, miR-204-y, miR-211-x, miR-211-z); 2) chromatophore development (miR-206-z, miR-206-y, miR-499-y, miR-1-z, miR-2188-x, miR-423-x); and 3) carotenoid metabolism (miR-204-x, miR-204-y, miR-499-y). This study demonstrates the potential role of miRNAs in red color formation and lays the foundation for the molecular mechanism of body color polymorphism in P. leopardus .

Preparation of super hydrophilic-underwater super oleophobic photoinduced self-cleaning Al2O3 @TiO2 ceramic membrane and separation performance of oil-in-water emulsion - Dongdong Wang; Likun Huang; Xinyi Miao; Xiyu Sun; Simin Zhou; Rui Zhao; Guangzhi Wang; Haiyang Sun; Shaofang Li; Zhe Li (Journal of Environmental Chemical Engineering, 2023)

Comparision of nitrogen removal characteristic and microbial community in freshwater and marine recirculating aquaculture systems - Wenqian Zhang; Bo Liu; Zhenzhu Sun; Tingyu Wang; Simin Tan; Xin Fan; Danyang Zou; Yutong Zhuang; Xinting Liu; Yizhu Wang; Yanyu Li; Kangsen Mai; et al. (Science of The Total Environment, 2023)

Vegetable extracts: Effective inhibitors of heterocyclic aromatic amines and advanced glycation end products in roasted Mackerel - Simin Zhang; Ruichun Wang; Junbo Chu; Chenyang Sun; Songyi Lin (Food Chemistry, 2023)

The potential mechanisms of skin wound healing mediated by tetrapeptides from sea cucumber - Zhihong Zheng; Na Sun; Zhiqiang Lu; Jingru Zheng; Simin Zhang; Songyi Lin (Food Bioscience, 2023)

A review of the development in shale oil and gas wastewater desalination - Simin Zhou; Likun Huang; Guangzhi Wang; Wei Wang; Rui Zhao; Xiyu Sun; Dongdong Wang (Science of The Total Environment, 2023)

Fabrication of high strength cold-set sodium alginate/whey protein nanofiber double network hydrogels and their interaction with curcumin - Sijie Wu; Lu Wang; Yingying Zhao; Bilian Chen; Dan Qiu; Peilong Sun; Ping Shao; Simin Feng (Food Research International, 2023)

Microwave-assisted co-precipitation preparation of CuFe2O4 photo-Fenton degradation tetracycline: Characterization, efficacy, stability in complex water quality and mechanism - Xiyu Sun; Guangzhi Wang; Likun Huang; Huanzhang Feng; Simin Zhou; Rui Zhao; Dongdong Wang; Zhe Li (Journal of Environmental Chemical Engineering, 2023)

Utilization of ovalbumin-propylene glycol alginate complex system for superior foam: The effect of pH-driven phase behavior - Xinyue Zhang; Zizhen Sun; Qi Zeng; Haobo Jin; Simin Wang; Yongguo Jin; Yu Hu; Zhaoxia Cai (Food Hydrocolloids, 2023)

Mercury isotope evidence for protracted North Atlantic magmatism during the Paleocene-Eocene Thermal Maximum - Simin Jin; David B. Kemp; Runsheng Yin; Ruiyang Sun; Jun Shen; David W. Jolley; Manuel Vieira; Chunju Huang (Earth and Planetary Science Letters, 2023)

Low-Cd wheat varieties and soil Cd safety thresholds for local soil health management in south Jiangsu province, east China - Pengjie Hu; Feng Tu; Simin Li; Yunjun Pan; Cheng Kong; Xumei Zhang; Shaohua Wang; Yongquan Sun; Dan Qiu; Longhua Wu; Yongming Luo; Peter Christie (Agriculture, Ecosystems & Environment, 2023)

SbWRKY55 regulates sorghum response to saline environment by its dual role in abscisic acid signaling - Yushuang Song; Hongxiang Zheng; Yi Sui; Simin Li; Fenghui Wu; Xi Sun; Na Sui (Theoretical and Applied Genetics, 2022)

A review on chemical and physical modifications of phytosterols and their influence on bioavailability and safety - Simin Feng; Liling Wang; Ping Shao; Peilong Sun; Chung S. Yang (Critical Reviews in Food Science and Nutrition, 2022)

Effects of Shear Stress and Salinity Stratification on Floc Size Distribution During the Dry Season in the Modaomen Estuary of the Pearl River - Jie Huang; Simin Wang; Xinran Li; Rongyao Xie; Jianxiong Sun; Benwei Shi; Feng Liu; Huayang Cai; Qingshu Yang; Zhaoyong Zheng (Frontiers in Marine Science, 2022)
The floc size distribution of fine cohesive sediments in estuaries varies spatiotemporally within assorted physical, chemical, and biological factors. However, the distribution of different floc fractions that are affected by shear stress and salinity stratification has not yet been thoroughly investigated. This study intends to clarify the floc size distribution within the influences of turbulent shear rate and salinity stratification, and the implications for the flocculation process during the dry season in the Modaomen Estuary of the Pearl River. The decomposition of multimodal floc size distributions (FSDs) indicates that the floc fractions were composed of macroflocs (Macro), microflocs (Micro), Flocculi, and primary particles (Pp). Macro generally existed among the upper and middle layers, but smaller flocs, i.e., Micro, Flocculi, and Pp, were mostly concentrated in the bottom layer. The results agreed that the flocculation and deflocculation processes were dominant in the upper and bottom layers, respectively. In response to strong turbulent shear rates, FSDs in the bottom layer skewed toward small sizes and had a dual-peak tendency with frequent floc exchanges between Pp and Micro, then being Pp-dominant but converting to Micro when turbulent shear rates decreased. With impeded vertical mixing by salinity stratification, the FSDs in the upper or middle layers skewed toward a larger particle size with single peaks and lack of exchange among different floc fractions, leading to Macro dominance with a larger volume concentration and median size. In addition, turbulence mixing dramatically interfered with the good mixing of floc fractions amidst the vertical water column, with a low-salinity condition greatly affecting the formation of Macro in the bottom layer within proper turbulent shear rates. This study explores the effects of shear stress and salinity stratification on the flocculation process in the Modaomen Estuary, which contributes to a better understanding of sediment movement in a complex estuarine environment.

SbbHLH85, a bHLH member, modulates resilience to salt stress by regulating root hair growth in sorghum - Yushuang Song; Simin Li; Yi Sui; Hongxiang Zheng; Guoliang Han; Xi Sun; Wenjing Yang; Hailian Wang; Kunyang Zhuang; Fanying Kong; Qingwei Meng; Na Sui (Theoretical and Applied Genetics, 2022)

Preparation of sludge-based materials and their environmentally friendly applications in wastewater treatment by heterogeneous oxidation technology - Xiyu Sun; Guangzhi Wang; Huanzhang Feng; Xinyi Miao; Simin Zhou; Dongdong Wang; Likun Huang; Kun Wang (Environmental Science and Pollution Research, 2022)

Rapid operation of a Tainter gate: generation process and initial upstream surge motion - Simin Sun; Xinqian Leng; Hubert Chanson (Environmental Fluid Mechanics, 2016)

Characteristics of clustered particles in skimming flows on a stepped spillway - Simin Sun; Hubert Chanson (Environmental Fluid Mechanics, 2013)